Pengaruh Relationship Marketing, Experiental Marketing dan Digital Payment Terhadap Customer Loyalty (Studi Pada Kopi Komunal di Kota Mataram) - Putu Ayu Chandra Utari, Ni (Postgraduate, University of Mataram, 2025)
This research aims to analyze the influence of Relationship Marketing, Experiential Marketing, and Digital Payment on Customer Loyalty at Kopi Komunal in Mataram City. The data collection method used a questionnaire with a sample of 100 respondents. The analysis method used multiple linear regression analysis with the Statistical Package For The Social Sciences (SPSS) tool. The research results show that Relationship Marketing has a positive and significant effect on Customer Loyalty. Second, Experiental Marketing has a positive and significant effect on Customer Loyalty. Third, Digital Payment has a positive and significant impact on Customer Loyalty. The research results can serve as a basis for developing more effective strategies to enhance Relationship Marketing, Experiential Marketing, Digital Payment, and Customer Loyalty.